Symbiotic Success: Unveiling the Crucial Link Between Human Resources Strategies and Elevated Customer Satisfaction an Analytical Study of a Sample of Small Companies - Lafta, Alaa Manea (Integrated Journal for Research in Arts and Humanities, 2024)
The study aims to understand the role of the availability of skilled people in marketing activities for Iraqi technology companies c to acquire nice hangs in Consumer behavior, which maintains the business enterprise’s position in the marketplace price stability It was obtained by conducting a survey, whereby the survey obtained various objectives and hypotheses. The important finding of study is that marketing activity is one of the most important functions in firms that are directly connected with the public, as that activity helps to create an enabling environment in which the public also accepts these firms’ products. The most important recommendation of the study is the importance of increasing the interest of Iraqi companies in marketing and human activities that can have a better analysis of consumer behavior and pursue best marketing practices of Iraqi industrial companies internationally between comparisons In sectors and obtain positive attitudes results related to customer satisfaction.